Prevalence of Non-strabismic Binocular Vision Dysfunction Among Optometry Students in Bangalore, India. - Dahal, Manish; Khatri, Bikash (Optometry & Visual Performance, 2019)
Purpose: Non-strabismic binocular vision dysfunctions (NSBVD) are common in the prepresbyopic population, often resulting in less productivity in academic and other near vision-oriented tasks. Optometrists provide comprehensive vision care to the public and are often the first practitioners to examine patients with binocular dysfunctions. Optometrists must begin to acquire skills to diagnose and manage binocular dysfunctions through clinical experience during their education. This project aimed to determine the prevalence of NSBVD among optometry students, as well as their awareness of the condition. Methods: Forty optometry students, ages 19 to 26, were recruited. Each subject was examined to investigate for the presence of NSBVD. Results: The mean age of the patients was 22 ± 2.5 years. The prevalence of non-strabismic accommodative dysfunction was 55%, vergence dysfunction was 73%, and oculomotor dysfunction was 15%. The most common NSBVD was accommodative insufficiency (30%), followed by accommodative excess (20%). Conclusion: This study indicates a high prevalence of accommodative and vergence dysfunction in the selected sample of optometry students. These preliminary results indicate a need for improved awareness, diagnosis, and management of binocular dysfunctions in order to increase the academic potential of these students and to enable their future participation in the clinical assessment of undiagnosed NSBVD.